Chimerism as a strategy to improve the resilience of boulder corals - Mendoza-Quiroz, Sandra; Miller, Margaret W.; Tecalco-Rentería, Raúl; Ramírez-Tapia, Gandhi Germán; Banaszak, Anastazia T. (Scientific Reports, 2025)
Chimeras form by the fusion of at least two distinct genets. Such genetic heterogeneity has been hypothesized to increase resilience of clonal invertebrates, and, given the changing environment of coral reefs, may provide important benefits in coral restoration. Intra- and interspecific pairs of six- and 18-month-old Orbicella faveolata and O. annularis recruits were actively staged in aquaria. Successful fusion was observed in intraspecific pairs, especially in the younger recruits of O. faveolata (70%). Fusion success between other intraspecific pairings ranged from 20 to 40%. Survival and growth of the fused chimeras were evaluated over two years following outplanting alongside large (> 1 cm diameter) and small (< 1 cm diameter) singleton recruits selected from the same cohorts. Chimeras showed 43–57% mortality over the first year, but no subsequent mortality and positive growth rates were maintained, even during the 6 months of the 2023 severe heatwave. Singletons of both size classes suffered continuous whole-colony mortality over the study period and negative growth rates during the heatwave. No chimeras formed between interspecific pairings over six months. This study provides important evidence of fusion success rates in Caribbean boulder corals and of the hypothesized greater resilience of chimeras in a restoration setting independent of colony size.